KEMAMPUAN MENELAAH STRUKTUR DAN KEBAHASAAN TEKS FABEL PADA SISWA KELAS VII SMP N 22 MEDAN TAHUN PEMBELAJARAN 2021/2022 - Oknanda, Hikmah; Umar, Azhar (Jurnal Komposisi, 2022)
This study aimed to describe the ability of students in grade VII of SMP Negeri 22 Medan to analyze the structure and language of fable texts. The method used was a descriptive method. The population of this study was all students in grade 7 of the 2020/2021 academic year, consisting of 8 classes with a total of 240 students. The sample of this study was class VII-5, which consisted of 30 students. The research instrument used was a test of analyzing fable texts. The results of the study showed that the ability of students in grade VII of SMP Negeri 22 to analyze the structure and language of fable texts was considered good with an average score of 82. This result was obtained based on the structure aspect which obtained an average score of 86, and the language aspect which obtained an average score of 79. Furthermore, the distribution table of percentage values of the ability of students to analyze the structure and language of fable texts in grade VII of SMP Negeri 22 Medan showed that 33% of them were categorized as very good, while 67% were categorized as good.